The Communication of Maccini Oto Youth Forum (FPM) in Realizing Islamic Brotherhood among Youth in Pangkajene Subdistrict, Pangkajene and Islands Regency. - Fahmi Hasbi; Abd. Rasyid Masri; Nurhidayat Muh. Said (Jurnal Mercusuar, 2022)
This research aims to: understand the communication patterns of the Maccini Oto Youth Forum (FPM) in realizing Youth Islamic Brotherhood (Ukhuwah Islamiyah) in the Pangkajene Subdistrict, Pangkajene and Kepulauan Regency. This study employs a qualitative descriptive research design located in the Pangkajene Subdistrict, Pangkajene and Kepulauan Regency. The approaches utilized are communication and sociological approaches. The primary data sources for this research are informants, with key informants being the leaders of the Maccini Oto Youth Forum (FPM) and conflicting youth. Additional informants include governmental, religious, and community figures. Secondary data sources encompass books, the internet, ebooks, journals, and other supplementary materials. The data collection methods involve several stages: observation, interviews, and documentation. Data analysis is carried out in three stages: Collecting, Reducing, Displaying, and Concluding. The results of this research reveal that the communication patterns employed by the Maccini Oto Youth Forum (FPM) to realize Youth Islamic Brotherhood include primary communication patterns, secondary communication patterns, linear communication patterns, and interactive communication patterns. The implications of this research underline that the success of the Maccini Oto Youth Forum (FPM) youth organization in achieving Youth Islamic Brotherhood is intricately linked with communication strategies and program activities. However, to enhance success, collaboration with the community and government agencies is essential. To mitigate conflicts among youth groups for the realization of Youth Islamic Brotherhood, it is imperative to implement various communication patterns, including primary, secondary, linear, and interactive communication patterns.